Translation and validation study of the Chen Internet Addiction Scale (CIAS)among Malaysian college students - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi; Musa, Ramli (Ektodermal Displazi Grubu - Türkiye, 2018)
Due to the convenience and availability of internet in universities, internet use has become one of the most common methods of entertainment and studying for college students. However, using the internet excessively leading to internet addiction may result in negative consequences such as decline in academic performance, social isolation, and emotional disturbances Hence there is a real need to have a validated scale to address this issue. The aims of this study are to translate and validate the Chen Internet Addiction Scale (CIAS) into Malay language (BM). Two forward and backward translations were done in BM, and its validation was determined by using confirmatory factor analysis. A total of 268 medical students were approached to represent Malaysian adult population for reliability and validity purposes. Reliability of the Malaysian version of Chen Internet Addiction Scale (CIAS) revealed excellent Cronbach’s alpha value of 0.89. Construct validity, evaluated using exploratory factor analysis, had good factor loadings for most of its 26 items except 4. These 4 items had been discussed thoroughly and few suggestions were highlighted. The Malaysian version of Chen Internet Addiction Scale is correctly and adequately translated to Bahasa Malaysia with high psychometric properties among the tested population. Further studies are needed to verify these preliminary outcomes especially for higher analysis such as confirmatory factor analysis to affirm the validity among Malaysian population